A comparison of transmission characteristics of Salmonella enterica serovar Enteritidis between pair-housed and group-housed laying hens - Thomas Ekelijn; Bouma Annemarie; Klinkenberg Don (Veterinary Research, 2011)
Abstract Human cases of bacterial gastro-enteritis are often caused by the consumption of eggs contaminated with Salmonella species, mainly Salmonella enterica serovar Enteriditis (Salmonella Enteritidis). To reduce human exposure, in several countries worldwide surveillance programmes are implemented to detect colonized layer flocks. The sampling schemes are based on the within-flock prevalence, and, as this changes over time, knowledge of the within-flock dynamics of Salmonella Enteritidis is required. Transmission of Salmonella Enteritidis has been quantified in pairs of layers, but the question is whether the dynamics in pairs is comparable to transmission in large groups, which are more representative for commercial layer flocks. The aim of this study was to compare results of transmission experiments between pairs and groups of laying hens. Experimental groups of either 2 or 200 hens were housed at similar densities, and 1 or 4 hens were inoculated with Salmonella Enteritidis, respectively. Excretion was monitored by regularly testing of fecal samples for the presence of Salmonella Enteritidis. Using mathematical modeling, the group experiments were simulated with transmission parameter estimates from the pairwise experiments. Transmission of the bacteria did not differ significantly between pairs or groups. This finding suggests that the transmission parameter estimates from small-scale experiments might be extrapolated to the field situation.